Analisis Pengaruh Financial distress, Internal control weakness, dan Auditor switch terhadap Restatement Laporan Keuangan: Perusahaan Perbankan Terdaftar di BEI 2020-2024 - Dora Insi Epriana; Winny Lian Seventeen; Seftya Dwi Shinta (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
This study aims to analyze the effect of financial distress, internal control weakness, and auditor switching on financial statement restatement in banking companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This research employs a quantitative approach using binary logistic regression. The sample was selected using purposive sampling, resulting in 22 companies with a total of 110 observations. The data used are secondary data obtained from financial statements and annual reports. The results show that partially, financial distress and auditor switching do not have a significant effect on financial statement restatement. In contrast, internal control weakness has a positive and significant effect on restatement, indicating that weaknesses in internal control systems increase the likelihood of financial reporting errors. Simultaneously, all independent variables significantly affect financial statement restatement. The Nagelkerke R Square value of 0.269 indicates that the model explains 26.9% of the variation in restatement, while the remaining 73.1% is influenced by other factors outside the model. These findings highlight the importance of effective internal control in maintaining the quality of financial reporting, particularly in the highly regulated banking sector